Astrocytes from lamina cribrosa are involved in the autoregulatory function of optic nerve head vessels in vitro - Feng, Xiaoxiao; Zhang, Wenjia; Wan, Tingting; Jiao, Kangwei; Zhang, Liwei; Li, Changhui; Xiao, Libo (Frontiers in Molecular Biosciences, 2025)
PurposeTo investigate the role of the lamina cribrosa (LC) astrocytes in the autoregulatory capacity of optic nerve head (ONH) vessels and to explore the underlying molecular mechanisms.MethodsThe Oxygen-glucose deprivation/reperfusion model (OGD/R) in vitro was constructed to examine the changes in cell morphology and protein expression in LC astrocytes. LC astrocytes were co-cultured with vascular smooth muscle cells (VSMCs) to detect the role of LC astrocytes in the autoregulatory function of vessels.ResultsThe partial pressure of oxygen (PO2) in the supernatant of LC astrocytes was significantly lower following OGD, and this reduction was more pronounced with longer OGD durations. OGD inhibited proliferation and promoted apoptosis in LC astrocytes, with longer OGD durations correlating with decreased proliferation and increased apoptosis. Reoxygenation following 1 h of OGD led to upregulation of GFAP, mTOR, cPLA2 protein expression and supernatant PGE2 concentration in LC astrocytes, an effect that can be attenuated by the mTOR inhibitor. Co-culturing with LC astrocyte resulted in increased expression of MYPT1 protein in VSMCs, and the VSMCs exhibited a relaxed morphology.ConclusionUnder in vitro OGD/R conditions, LC astrocyte were activated through the mTOR pathway, leading to increased secretion of PGE2, which locally regulates the dilation of VSMCs. In conclusion, LC astrocytes may regulate local blood flow in the ONH.